2021
DOI: 10.1519/jsc.0000000000003105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Selected Lymphocyte (CD45+) Subset Distribution in Capillary Blood of Young Soccer Players

Abstract: Nowak, R, Kostrzerwa-Nowak, D, and Buryta, R. Analysis of selected lymphocyte (CD45+) subset distribution in capillary blood of young soccer players. J Strength Cond Res 35(8): 2279–2286, 2021—Mechanisms responsible for increasing athletes' physical capacity and induction of exercise-induced immunosuppression processes are not fully understood. The aim of the study was to monitor changes in percentages of lymphocyte subsets: T, Th, Tc, B, and NK cells in capillary blood of junior soccer players. Ten subjects m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…The CD4 + FoxP3 + (Treg) cells are also involved in post-effort immune modulation because of their role as central anti-inflammatory regulators of the immune response [ 16 , 18 ]. The participation of T cells in the modulation of immunity during maximal effort has been described in athletes [ 19 , 20 , 21 , 22 ]. On the other hand, numerous physically active young men, even though they are not professional athletes, use professional training programs to improve their physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…The CD4 + FoxP3 + (Treg) cells are also involved in post-effort immune modulation because of their role as central anti-inflammatory regulators of the immune response [ 16 , 18 ]. The participation of T cells in the modulation of immunity during maximal effort has been described in athletes [ 19 , 20 , 21 , 22 ]. On the other hand, numerous physically active young men, even though they are not professional athletes, use professional training programs to improve their physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies suggest that neutrophils are mobilized in response to exercise-induced muscle damage 5 , 24 , we did not observe significant changes in total WBC counts or in granulocyte distribution in subjects after post-match recovery. While changes in the post-match distributions of different WBC subsets (namely lymphocytes and monocytes) were observed among junior soccer players 45 , it was not confirmed during long-term observation among senior soccer players. This suggests that the adaptive mechanism and adequate recovery are important factors in immunobalance as represented by the WBC distribution in capillary blood.…”
Section: Discussionmentioning
confidence: 76%
“…From this point of view, a lack of significant changes after the recovery time might be related to the biological adaptation of the immune system to inflammation pathways involved in the post-effort immune response. It seems that the cell balance in capillary blood is disordered only in non-professional athletes and after inadequate recovery time 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The lower expression of WBC, LYM, and LYM% in the HL group compared with that of the HH group suggests that soldiers with higher altitude running speeds have lower levels of inflammatory stress and better antioxidant capacity (Xiong et al, 2020). Kostrzewa et al confirmed that the increase in WBC count after exercise is related to the immune response and is not solely caused by dehydration (Nowak et al, 2020). WBC counts often decline after prolonged training, and high altitudes are associated with an inflammatory response (Galun et al, 1987).…”
Section: Discussionmentioning
confidence: 99%